1, 由(1+tanA) (1+tanB)=2
tanA+tanB+tanAtanB=1
經(jīng)通分后可以得到
sinAsinB+sinAcosB=cosAcosB-sinAsinB
sin(A+B)=cos(A+B)
A+B=pi/4 或 A+B=pi+pi/4
因 A、B均為銳角
因此 A+B=pi/4
2,由已知條件,可以得到
1/a-1/b=1/b-1/c
經(jīng)通分得
2ac= b(a+c)
a^2+c^2=a^2+c^2+b(a+c)-2ac
a^2+c^2=(a-c)^2+ b(a+c)
因?yàn)?a-c)^2>=0,而且a+c>b
a^2+c^2>b^2
因此 可以得知 B
sin(A+B)cosA=2sinAcos(A+B)
sin(A+B)cosA-sinAcos(A+B)= sinAcos(A+B)
sinB=sinAcos(A+B)
3sinB=3sinAcos(A+B)
=sinAcos(A+B)+2sinAcos(A+B)
= sinAcos(A+B)+sin(A+B)cosA
=sin(A+A+B)
=sin(2A+B)
因此得證3sinB=sin(2A+B)